Comprehensive Study and Noise Analysis of GeSn-based p-n-p Heterojunction Phototransistors for Efficient Detection - Kumar, Harshvardhan; Basu, Rikmantra (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
This work presents analytical study of gain, noise behaviour, absorption coefficient and optical responsivity of Ge 1-x Sn x -based p-n-p Heterojunction Photo-Transistor. Estimated results ensure that HPTs can be used as an alternative of existing III-V based photodetectors.